Child Sexual Abuse and the Media - Stelzmann, Daniela; Ischebeck, Josephine (2022)
Spectacular cases of child sexual abuse (CSA) dominate media coverage again and again, shaping our knowledge about a topic that is as sensitive as it is taboo. To date, a scholarly overview of the current state of media coverage of SBC has been lacking. This book attempts to shed light on the connections between SBCs and the media in a variety of ways, incorporating different studies and perspectives from practitioners. It thus provides a comprehensive overview of relevant issues raised in the context of CSA and the media.